(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Medicinal values of spices are quite remarkable due to which they are considered safe and effective against many infections and diseases. Various spices show varied levels of pharmacological activity making them as powerful therapeutic agent. Piper cubeba L.f. (Piperaceae), known as cubeb, is a popular traditional herbal medicine used for the treatment of many diseases, especially digestive and respiratory disorders. The plant is rich in essential oil. This study deals with Qualitative & quantitative estimation of phytochemicals from Piper cubeba. The results showed that flavonoid, diterpene, phenol, protein, carbohydrate & saponins. Thin layer chromatography suggest that extract contain gallic acid and quercetin as the Rf value of standard coincides with extract. Total phenol & flavonoid content in hydroalcoholic extract was found to be 0.578 and 0.867 mg/100mg of dried extract. Thus, from the results it can be interpreted that the hydroalcoholic extract of Piper cubeba contains appreciable amount of phytochemicals thus it can be further investigated for pharmacological activity.